2016
DOI: 10.1039/c5ta09924b
|View full text |Cite
|
Sign up to set email alerts
|

Composites of metal–organic frameworks and carbon-based materials: preparations, functionalities and applications

Abstract: This review summarizes the recent progress in preparations, functionalities and applications of composites of metal–organic frameworks (MOFs) and carbon-based materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
180
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(186 citation statements)
references
References 310 publications
2
180
0
4
Order By: Relevance
“…Traditionally, PC can be obtained via various methods, such as the direct heat treatment of organic precursors, hard template or nanocast methods, and soft template methods. [4,21,[27][28][29][30][31] Since the report on the MOF-templated synthesis of PC in 2008, [32] a large number of studies have been reported on the use of MOFs as suitable precursors/templates for carbon synthesis. [23,25,26] Metal-organic frameworks (MOFs) have drawn wide research interest as a novel class of porous materials that are crystalline materials consisting of metal ions and organic ligands.…”
mentioning
confidence: 99%
“…Traditionally, PC can be obtained via various methods, such as the direct heat treatment of organic precursors, hard template or nanocast methods, and soft template methods. [4,21,[27][28][29][30][31] Since the report on the MOF-templated synthesis of PC in 2008, [32] a large number of studies have been reported on the use of MOFs as suitable precursors/templates for carbon synthesis. [23,25,26] Metal-organic frameworks (MOFs) have drawn wide research interest as a novel class of porous materials that are crystalline materials consisting of metal ions and organic ligands.…”
mentioning
confidence: 99%
“…Pierwsza z nich, konfrontacyjna, polega na wyborze lepszego z nich i wypieraniu go z danej dziedziny, natomiast druga to droga synergiczna, której zadaniem jest wykorzystanie pożądanych cech obu grup materiałów. Jest to najprostsza metoda łagodząca wady poszczególnych składników i integrująca ich korzystne właściwo-ści [21]. W tym przypadku najbardziej oczywistym rozwiązaniem jest stworzenie kompozytu.…”
Section: Materiały Kompozytoweunclassified
“…są nieprzewodzące, nieodporne na wodę/parę wodną, wykazują słabą odporność mechaniczną. Ponadto, posiadają wąskie mikropory, które są zaletą w przypadku wychwytywania cząsteczek adsorbatu, jednakże znacznie spowalniają proces przenoszenia masy, a tym samym wydajność adsorpcji [21]. Na szczęście, tworzenie kompozytów MOF z innymi komponentami pozwala wykorzystać ich zalety przy jednoczesnym pominięciu wad [26].…”
Section: Materiały Kompozytoweunclassified
See 2 more Smart Citations